PENGARUH EMOTIONAL QUOTIENT DAN SELF EFFICACY TERHADAP KINERJA AUDITOR (Studi Kasus Kantor Akuntan di Surakarta dan Yogyakarta) - LMS Kristiyanti (Jurnal Akuntansi dan Pajak, 2015)
This research aims to give empirical proof on Emotional of Quotient and Self Efficacy towards auditor performance.This research is motivated by a fact that for competing with other professionals  and getting a success can be reached not only by technical knowledge but also by other factors such as Emotional Quotient and Self Efficacy. The objects of this research and the respondent are the auditors of Public Accountant offices that are located in Solo and Yogyakarta. The methods of collecting data by questionnaires are sent directly to Public Accountant offices in Surakarta area.. While for the respondents at public accountant offices in Yogyakarta, the questionnaires are sent by courier service. The number of auditors participating in this research is 35. .Data that have been collected are primary data that are then analyzed using computer program of SPSS Version 17.0The result of this research shows that emotional quotient and self efficacy individually and simultaneously influence towards auditor performance both positively and significantly.  Values of influence on free variables are emotional quotient and self efficacy towards bound variables are auditor performance is 77,9 %, while the rest is 22,1 % that is influenced by other factors that are not explained in this research. Keywords: emotional quotient, self efficacy, and  auditor performance